How to improve the moral capital of civil society organizations? Some ordonomic suggestions - Stefan Hielscher; Jan Winkin; Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2017)
Civil Society Organizations (CSOs) are indispensable watchdogs against corrupt practices and global challenges found in complex, modern societies. Yet sometimes, CSOs themselves can struggle to live up to the ambitious standards they demand of others, such as responsible advocacy, ethical fundraising, and meaningful participation of stakeholders. In this discussion paper, we present the practical implications of our recently published research, which suggests that strengthening the rules of 'fair competition' among CSOs is a promising avenue to increase their credibility. – – Zivilgesellschaftliche Organisationen (ZGO) sind für die Bewältigung zahlreicher globaler Herausforderungen der modernen Gesellschaft unverzichtbar. Allerdings fällt es ZGO bisweilen schwer, jene ambitionierten Standards selbst einzuhalten, die sie völlig zu Recht von anderen Akteuren einfordern, etwa im Hinblick auf eine verantwortungsvolle Interessenvertretung, ethisches Fundraising oder die Einbeziehung wichtiger Stakeholder-Gruppen in die organisationale Willensbildung. In diesem Artikel diskutieren wir die praktischen Implikationen der jüngst am Lehrstuhl für Wirtschaftsethik entwickelten und in internationalen Fachzeitschriften veröffentlichten ordonomischen Forschungsbeiträge. Unsere zentrale Schlussfolgerung besteht darin, die Regeln für einen 'fairen Wettbewerb' zwischen CSOs zu verbessern, um so die Glaubwürdigkeit des gesamten CSOSektors zu stärken.
urn:nbn:de:gbv:3:2-75483
Keywords: 330; Civil Society; Responsible Advocacy; Competition; Self-Regulation; Zivilgesellschaft; Responsible Advocacy; Wettbewerb; Selbstregulierung